2010
DOI: 10.1007/s00438-010-0535-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes that affect sensitivity to 5-bromodeoxyuridine in the yeast Saccharomyces cerevisiae

Abstract: Small molecules that exhibit biological effects have been successfully used to study various biological phenomena. 5-Bromodeoxyuridine (BrdU) is a thymidine analog that affects various biological processes, such as cellular differentiation and cellular senescence in cultured mammalian cells. Although BrdU is thought to modulate these phenomena by changing chromatin structure and gene expression, the molecular mechanisms for the action of BrdU are not understood well. To analyze the molecular mechanisms of BrdU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This suggests that the J-insertion machinery may require more than one unmodified T to act, even if J is already present in DNA. These results make it unlikely that the BrdU effect on J is due to the type of chromatin alterations found by BrdU incorporation in yeast, which is highly dependent on DNA sequence (Miki et al, 2010; Fujii et al, 2010). …”
Section: Discussionmentioning
confidence: 95%
“…This suggests that the J-insertion machinery may require more than one unmodified T to act, even if J is already present in DNA. These results make it unlikely that the BrdU effect on J is due to the type of chromatin alterations found by BrdU incorporation in yeast, which is highly dependent on DNA sequence (Miki et al, 2010; Fujii et al, 2010). …”
Section: Discussionmentioning
confidence: 95%
“…In addition, the S. cerevisiae deletion libraries are useful and widely used tools for chemical screenings to perform drug sensitivityrelated genome studies. Commonly, toxicogenomic studies employ either the haploid gene deletion collections with no gene expression (Parsons et al, 2004;Arita et al, 2009;Zhou et al, 2009;Costanzo et al, 2010;Emadi et al, 2010;Fujii et al, 2010;Stefanini et al, 2010;Kwak et al, 2011) or the heterozygous diploid collection in which gene expression is reduced (also referred to as haploinsufficiency profiling; Giaever et al, 1999;Baetz et al, 2004;Hillenmeyer et al, 2008;Bendaha et al, 2011;Hoepfner et al, 2012). The aim of these approaches is to establish chemical-genetic profiles of specific compounds such as arsenic or naphthoquinones Emadi et al, 2010) or on a larger scale to develop genetic interaction maps (Parsons et al, 2004;Costanzo et al, 2010), both of which can lead to the identification of the compound's target pathways or proteins.…”
Section: Yeast Researchmentioning
confidence: 99%
“…We have previously isolated the strain of the yeast Saccharomyces cerevisiae that incorporates BrdU, and shown that BrdU suppresses the growth of yeast [24]. Furthermore, we showed a possible implication of histone modifications in the regulation of the sensitivity to BrdU in yeast [25,26]. Here, we examined the roles of the histone tails in the action of BrdU, and found that a short basic domain in the N‐terminal tail of histone H2B, which is termed the HBR (histone H2B repression) domain, is involved in the action of BrdU [27].…”
Section: Introductionmentioning
confidence: 99%